2022
DOI: 10.1136/rmdopen-2022-002602
|View full text |Cite
|
Sign up to set email alerts
|

Is there a mitochondrial DNA haplogroup connection between osteoarthritis and elite athletes? A narrative review

Abstract: Elite athletes are at greater risk of joint injuries linked to the subsequent risk of developing osteoarthritis (OA). Genetic factors such as mitochondrial (mt) DNA haplogroups have been associated with the incidence/progression of OA and athletic performance. This review highlights an area not yet addressed: is there a common pattern in the mtDNA haplogroups for OA occurrence in individuals and elite athletes of populations of the same descent? Haplotypes J and T confer a decreased risk of OA in Caucasian/Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…His team has been working on a series of studies on the pathogenesis, risk factors, biomarkers, and treatment of OA. In a recent study, they identified single nucleotide polymorphism genes and mitochondrial DNA haplogroups as biomarkers for early prediction of the progression of knee OA through machine learning ( Bonakdari et al, 2022 ; Martel-Pelletier and Pelletier, 2022 ). Highly cited literature can be considered the most valuable and influential research in the field, so new researchers can read these papers before further research ( Table 5 ; Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…His team has been working on a series of studies on the pathogenesis, risk factors, biomarkers, and treatment of OA. In a recent study, they identified single nucleotide polymorphism genes and mitochondrial DNA haplogroups as biomarkers for early prediction of the progression of knee OA through machine learning ( Bonakdari et al, 2022 ; Martel-Pelletier and Pelletier, 2022 ). Highly cited literature can be considered the most valuable and influential research in the field, so new researchers can read these papers before further research ( Table 5 ; Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 In KOA, in vitro studies have demonstrated the presence of mitochondrial dysfunction in chondrocytes due to mtDNA mutations, which may affect several pathways related to cartilage degradation. [41][42][43] In addition, mtDNA can also be involved in the activation of AIM2 inflammasome. 44 While mitochondria generate ATP to meet the energy needs of the body, they also generate reactive oxygen species (ROS) radicals to damage themselves.…”
Section: Mitochondria -Aim2mentioning
confidence: 99%